Influence of rheumatoid factor levels and TNF inhibitor structure on secondary nonresponse in rheumatoid arthritis patients - Plasencia-Rodríguez, Chamaida; Martínez-Feito, Ana; Novella-Navarro, Marta; Pérez De Diego, Rebeca; Bonilla, Gema; Gehin, Johanna Elin; Villalba-Yllán, Alejandro; Nuño, Laura; Pascual-Salcedo, Dora; Nozal, Pilar; Almirón, Mariana Díaz; Balsa, Alejandro (Frontiers in Medicine, 2024)
Background The EXXELERATE study revealed poorer clinical outcomes in patients treated with adalimumab (ADL) and baseline rheumatoid factor (RF) above 203 IU/mL. However, responses were similar in patients treated with certolizumab pegol (CZP) regardless of RF levels. Objectives This study investigated the impact of RF levels >203 IU/mL on TNF inhibitors (TNFi) serum levels and the association with secondary nonresponse in RA patients treated with TNFi. Methods We performed an observational ambispective study with RA patients treated with infliximab (IFX), ADL, or CZP. Patients were stratified according to baseline RF levels: ≤ or >203 IU/mL. After 6 months, serum drug levels and antidrug antibodies were measured, and reasons for discontinuation were collected. Results We included 170 RA patients: 90 (53%) received IFX, 48 (28%) ADL, and 32 (19%) CZP. While CZP serum levels did not differ between RF groups at 6 months (p = 0.6), RF levels >203 IU/mL were linked to lower serum drug levels in patients treated with IFX (p = 0.09) or ADL (p = 0.02). Secondary nonresponse was 3.6 times higher in patients with high versus low RF levels in patients under IFX or ADL. However, the reasons for withdrawal were not affected by RF levels in patients treated with CZP. Conclusion Baseline RF above 203 IU/mL is associated with lower serum drug levels and an increased risk of discontinuation due to secondary nonresponse in patients treated with IFX or ADL. In contrast, drug levels and clinical outcomes are not significantly impacted by baseline RF levels in patients under CZP.